Activity patterns and temporal niche partitioning in sympatric red‐legged and red‐necked pademelons. (24th December 2021) - Smith, Lucy E. V.; Andrew, Nigel R.; Vernes, Karl
Abstract: Temporal partitioning between ecologically similar species facilitates co‐occurrence and can influence the structure of mammalian assemblages. We studied diel activity patterns of two sympatric forest‐dwelling wallabies, the red‐legged pademelon ( Thylogale stigmatica ) and red‐necked pademelon ( Thylogale thetis ) in eastern Australia to better understand spatiotemporal partitioning between these closely related macropods. Temporally, both species displayed strongly crepuscular activity patterns typical of many macropod species; however, compared with T. thetis, T. stigmatica was less active during evening twilight and more active in the period prior to dawn. Spatially, T. stigmatica used dense forest cover exclusively throughout the 24‐hour cycle, while T. thetis divided its habitat spatiotemporally, spending the diurnal period under forest cover and the nocturnal period on pasture beyond the forest edge. In practical terms, this meant that T. stigmatica and T. thetis were fully spatially segregated at night, during the period they would be likely to do most of their foraging. We propose that the spatiotemporal partitioning observed is niche partitioning, and provides a mechanism for the co‐occurrence of these closely related species.